The professional interactions between speech language therapist and dentist - Martina Costanzo; Francesco Puleio; Roberto Lo Giudice; Angela Alibrandi; Ilenia Campione (Open Exploration Publishing Inc., 2024)
Aim: This study investigates the collaborative efforts between speech language therapists and dentists to address the challenges faced by patients with concurrent dental and speech issues. It underscores the importance of understanding the complex interactions within the craniofacial system and its implications for both oral health and communication abilities. Methods: A questionnaire-based research was conducted involving speech language therapists and dentists, using Google Forms as the medium of data collection. This study was disseminated through professional networks, where practitioners provided information on their demographics, practices of collaboration, and the perceived advantages of such interdisciplinary work. All ethical standards were adhered to, ensuring the confidentiality and informed consent of the participants. Results: The findings indicate that dentists, often see first patient visits beyond recommended ages primarily for existing conditions, deviating from preventive norms. About half communicate monthly with speech language therapists, revealing gaps in early care and collaboration. Speech language therapists focus on language disorders and orofacial myofunctional disorders (SMOF), with 37% collaborating frequently with dentists. This interaction highlights the potential for enhanced patient outcomes through interdisciplinary cooperation. Despite these challenges, both groups acknowledged the benefits of their collaborative efforts. Conclusions: The partnership between speech language therapists and dentists represents a vital area of healthcare, aimed at tackling the complex issues of oral health and communication through a multidisciplinary approach. Although obstacles in collaboration were identified, the positive outcomes observed from such partnerships emphasize the importance of developing a unified framework to improve integrated healthcare delivery in the future.